Kampo herbal ointments for skin wound healing - Paul-Traversaz, Manon; Umehara, Kaoru; Watanabe, Kenji; Rachidi, Walid; Sève, Michel; Souard, Florence (Frontiers in Pharmacology, 2023)
The management of skin wound healing problems is a public health issue in which traditional herbal medicines could play a determining role. Kampo medicine, with three traditionally used ointments, provides interesting solutions for these dermatological issues. These ointments named Shiunkō, Chuōkō, and Shinsen taitsukō all have in common a lipophilic base of sesame oil and beeswax from which herbal crude drugs are extracted according to several possible manufacturing protocols. This review article brings together existing data on metabolites involved in the complex wound healing process. Among them are representatives of the botanical genera Angelica, Lithospermum, Curcuma, Phellodendron, Paeonia, Rheum, Rehmannia, Scrophularia, or Cinnamomum. Kampo provides numerous metabolites of interest, whose content in crude drugs is very sensitive to different biotic and abiotic factors and to the different extraction protocols used for these ointments. If Kampo medicine is known for its singular standardization, ointments are not well known, and research on these lipophilic formulas has not been developed due to the analytical difficulties encountered in biological and metabolomic analysis. Further research considering the complexities of these unique herbal ointments could contribute to a rationalization of Kampo’s therapeutic uses for wound healing.